2021
DOI: 10.1038/s41598-020-80293-2
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic functional connectivity supports the configuration of brain networks associated with creative cognition

Abstract: Creative cognition is recognized to involve the integration of multiple spontaneous cognitive processes and is manifested as complex networks within and between the distributed brain regions. We propose that the processing of creative cognition involves the static and dynamic re-configuration of brain networks associated with complex cognitive processes. We applied the sliding-window approach followed by a community detection algorithm and novel measures of network flexibility on the blood-oxygen level depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 143 publications
0
14
0
Order By: Relevance
“…Growing evidence demonstrated that the fluctuations in FC are of neural origin and are also even more prominent during the resting period when mental activity is unconstrained. Temporal variability of the dynamic brain activity is related closely to various neurophysiological activities, including working memory ( Shunkai et al, 2021 ), vision ( Di and Biswal, 2020 ), and cognition ( Patil et al, 2021 ). Therefore, recent studies have shown that the dynamics of brain activity can better reflect neural activity.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence demonstrated that the fluctuations in FC are of neural origin and are also even more prominent during the resting period when mental activity is unconstrained. Temporal variability of the dynamic brain activity is related closely to various neurophysiological activities, including working memory ( Shunkai et al, 2021 ), vision ( Di and Biswal, 2020 ), and cognition ( Patil et al, 2021 ). Therefore, recent studies have shown that the dynamics of brain activity can better reflect neural activity.…”
Section: Introductionmentioning
confidence: 99%
“…These shifts in network topology fall along an axis defined by two extremes: segregated states in which regions are strongly connected to other regions within tight-knit ‘communities’ and weakly connected outside these communities, and integrated states that refer to strong functional connections between regions of different communities ( Sporns, 2013 ). There is now ample evidence from a range of studies that demonstrates brain network reconfiguration as a function of cognitive performance ( Bassett et al, 2011 , 2015 ; Braun et al, 2015 ; Fransson et al, 2018 ; Hearne et al, 2017 ; Ito et al, 2020 ; Mohr et al, 2016 ; Patil et al, 2021 ; Shine & Poldrack, 2018 ). Hence, the flexibility of the brain to shift between segregated and integrated states is inherently important in understanding brain function, but the underlying neural mechanism that gives rise to the flexibility in brain states is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…By partitioning fMRI images into time windows, the interconnections between brain regions can be better understood. Dynamic reconfigurations are more sensitive and able to detect more changes in human brain activity than static reconfigurations (Patil et al, 2021 ). whether static or dynamic, at rest or task-based, accurately identifying the altered functional connectivity generated by ADHD or any other specific disorder is a critical endeavor that may reveal the disorder's causative factors.…”
Section: Introductionmentioning
confidence: 99%